Alumni Dan Stakeholder (Studi Terhadap Kepuasan Dan Harapan Stakeholder Terhadap Alumni) - Irma Yusriani Simamora; M. Mukhtaruddin (Universitas Islam Negeri Sumatera Utara, 2019)
This research is backed by the importance of conducting a search about the satisfaction and expectation of stakeholders on alumni Department of Islamic Broadcasting of the Faculty of Da'wah and communication of North Sumatera State Islamic University. The type of research used is quantitative research. The population in this study is an alumnus of the Islamic Broadcasting Communications department FDK UIN SU. Sampling using probability sampling techniques is performed with methods simple random sampling. The data collection in this study is done by means of questionnaire techniques, Interviewer, and secondary data. Prior to conducting hypotheses, the earlier test for validity and reliability. The prerequisite test results show valid and reliable results. Testing hipthesis Using Test T and Test F. Based on the results of T test of several indicators of integrity, professional, leadership, technological ability, and foreign language ability can be concluded that has an influence on satisfaction Stakeholders. Based on test F results against several indicators of integrity, professional, leadership, technological ability, and foreign language ability can be concluded that together (simultaneous) affects stakeholder satisfaction.